Analysis of Urban Built Environment Impacts on Outdoor Physical Activities—A Case Study in China - Li, Bo; Liu, Qiuhong; Wang, Tong; He, He; Peng, You; Feng, Tao (Frontiers in Public Health, 2022)
Outdoor physical activities can promote public health and they are largely influenced by the built environment in different urban settings. Understanding the association between outdoor physical activities and the built environment is important for promoting a high quality of life. Existing studies typically focus on one type of outdoor activity using interview-based small samples and are often lack of systematic understanding of the activities’ intensity and frequency. In this study, we intend to gain deeper insight into how the built environment influences physical activities using the data extracted from individual’s wearables and other open data sources for integrated analysis. Multi-linear regression with logarithm transformation is applied to perform the analysis using the data from Changsha, China. We found that built environment impacts on outdoor physical activities in Changsha is not always consistent with similar studies’ results in other cities. And the most effective measures to promote outdoor physical activities are the provision of good arterial and secondary road networks, community parks, among others in Changsha. The results shed light on future urban planning practices in terms of promoting public health.